Delivering the promise of the Sendai Framework for Disaster Risk Reduction in fragile and conflict-affected contexts (FCAC): A case study of the NGO GOAL's response to the Syria conflict. (April 2021) - Patel, Sonny S.; McCaul, Bernard; Cáceres, Gabriela; Peters, Laura E.R.; Patel, Ronak B.; Clark-Ginsberg, Aaron
Abstract: The Sendai Framework for Disaster Risk Reduction (SFDRR) has helped to reduce global disaster risk, but there has been a lack of progress in disaster risk reduction (DRR) for people living in fragile and conflict affected contexts (FCAC). Given the mounting evidence that DRR cannot be implemented through conventional approaches in FCAC, serious efforts must be made to understand how to meet SFDRR's goals. This paper offers a case study of international non-governmental organization GOAL's programming that responds to the protracted crisis in Syria, with a critical discussion on SFDRR and how to adapt humanitarian relief and disaster resilience. Highlights: The current SFDRR framework risks leaving populations in FCAC behind. Systems thinking can help to reduce risk and build resilience in FCAC to progress SFDRR. Highly adaptive programs are essential to engage local actors over the long term.